ETR300 Froozy Food Trading / Muhammad Yusri Muhammad Yusof... [et.al] - Muhammad Yusof, Muhammad Yusri; Mohd Zaki, Nadiah; Toto, Aryanti; Azmi, Nur Syafiqa Azlin; Jamahushaini, Nur Syafiqah (2010)
The name of our company is Froozy Food Trading. The top management is very important to responsible for setting quantifiable, measurable and attainable objectives. This is for the top management to achieve the objective of the company for run smoothly. This is our responsibility for being top management committee.For" Froozy Food Trading \ our policy is developed as guideline for our daily operation of the company due to maximise profit and to supply fresh food to customers. Our major business activity is we are selling frozen food.This business place is at NO. 69, Ground and Second Floor, Desa llmu Phase II, Jalan Datuk Mohd Musa, 93400, Kota Samarahan, Sarawak. If not have problem by blessing from God our business will open 1st January 2011.